Tannin acid induced anticorrosive film toward stable Zn-ion batteries - Zhang, Peng-Fang; Wu, Zhenzhen; Zhang, Shao-Jian; Liu, Ling-Yang; Tian, Yuhui; Dou, Yuhai; Lin, Zhan; Zhang, Shanqing (Nano energy, 2022)
Aqueous Zn-ion batteries (AZIBs) have been regarded as a promising next-generation energy storage system. However, the poor reversibility of Zn anodes with serious dendrite growth and parasitic reactions degrades the battery performance. Inspired by the anticorrosion strategy for metal protection, an extremely simple and cost-effective method of soaking Zn plate in tannin acid (TA) solution is applied to design ZnTA anticorrosive film on Zn anodes. Robust chemical interaction between Zn and phenolic hydroxyl groups in TA molecules endows ZnTA with the excellent film-forming capacity of ensuring uniform surface and desirable coverage on Zn anodes. A remarkable suppression of parasitic hydrogen evolution during Zn plating is available by ZnTA@Zn anodes, evidenced by in-situ electrochemical gas chromatography (EC-GC). The Symmetric cells with ZnTA@Zn anodes show long-term stability of over 4500 cycles under an ultra-high current density of 30 mA cm−2, verifying the excellent reversibility ZnTA@Zn anodes. Besides, ZnTA anticorrosive film also demonstrates significant capacity to suppress the Zn corrosion resulted from shuttling polyiodide. Consequently, highly-reversible Zn-I2 batteries with excellent rate performance and ultra-long lifespan (20,000 cycles at 6 A g−1) are achieved with ZnTA@Zn anodes. This finding emphasizes the protective mechanism of anticorrosive films against electrolyte/polyiodide corrosion which contributes to the highly-reversible Zn anodes. An anti-corrosion strategy was applied to build an anti-corrosive film on the Zn surface by a tannin acid (TA) solution. The in-situ generated ZnTA anti-corrosive film significantly suppresses the dendrites formation, H2 evolution, and parasitic by-products generation. The ZnTA modified Zn anode in Zn-I2 full batteries exhibits remarkable potential in ultra-long cycling life (20000 cycles) and outstanding electrochemical performance. [Display omitted] •Tannin acid (TA) would in-situ construct a ZnTA anti-corrosive film on Zn anode.•The ZnTA film suppresses dendrite formation and parasitic H2 evolution.•The ZnTA-modified Zn anode delivers an ultra-high current density and ultra-stability.•The ZnTA film suppresses polyiodide corrosion, endowing Zn-I2 full batteries with an ultra-long lifespan of 20000 cycles.